To Assess the Relation between Fingerprint Patterns and Blood Groups - Mujeeb ur Rehman Sahito, Umbreen Bano, Noor ul Ain Zardari, Asad Ali Zardari, Shagufta Shaheen Qureshi, Asadullah Yousfani Palli (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: One of the greatest ways to identify a person is through their unique fingerprint pattern. They were already in place during the fetal stage and will never alter course or alignment over an individual's lifetime. The ABO and Rh blood types are being explored for the present inquiry, among other patterns of blood grouping. This study included a theoretical effort to link fingerprint patterns to gender and blood grouping. Objectives: It is necessary to examine the fingerprint patterns of people who have certain ABO and Rh blood types to discover Finding any correlation between ABO and Rh blood classes and finger-print patterns Materials and Methods: This study, conducted at the Peoples University of Medical and Health Sciences for Women Shaheed Benazir Abad, Sindh Pakistan, featured around 200 MBBS and BDS students with various blood types. Loops, whorls, and arches were the three types of fingerprints that were got from all the fingers. Results: Following the 'whorling' and 'arches' patterns, the 'loop' pattern was the most common. People with an 'O positive' blood type had the highest number of 'loop' varieties. Conclusion: It was shown that fingerprint morphology and blood type were linked in an existing investigation. Several interesting correlations between blood type distribution patterns and the distribution of human fingerprints were discovered.